Character Building Di Abad 12 Masehi: Kajian Dan Analisis Pendidikan Akhlak dalam Kitab Ta’lim Muta’Alim - Binti Su’aidah Hanur; Titik Widayati (Universitas Islam Lamongan, 2018)
In line with the vast development of science and technology, it is needed education development which in accordance with the need of current development by considering its positive and negative impacts. The process of education on the attitude or moral values got more attention in 12th century. He was Az-Zarnuji, the author of Ta’lim Muta’alim. This paper tries to dig Az-Zarnuji thought written on His Book mainly about moral education which well known by character building